Productive performance of strawberry in function of organic fertilizer and rock waste in planting - Camargo, Cristhiano Kopanski; Resende, Juliano Tadeu Vilela de; Camargo, Letícia Kurchaidt Pinheiro; Figueiredo, Alex Sandro Torre; Zanin, Daniel Suek (Semina: Ciências Agrárias, 2012)
The organic agriculture has been increasing in recent years, mainly because it is a production system that is socially, economically and ecologically correct. Mineral nutrition in alternative production systems is a determining factor for the success of crops. This study aimed to evaluate desirable agronomic traits of strawberry under different levels of cattle manure and rock waste. The experiment was conducted in the Department of Vegetable Crops in the UNICENTRO Guarapuava / PR. The fruits were collected from October 2008 to January 2009. We used the following treatments: 0, 50 and 100 t ha-1 of cattle manure and 0, 2, 4 and 6 t ha-1 of rock waste. The variables were evaluated productivity, commercial production and average mass of fruits. The average mass of fruit was not influenced by levels and sources of fertilizer. The results have revealed that both productivity and the commercial production of fruits performed better in the association of higher levels of cattle manure with intermediate levels of rock waste.